2018
DOI: 10.1093/tropej/fmy050
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of uptake of newly introduced vaccines in Malawi – monovalent human rotavirus and pneumococcal conjugate vaccines: Evidence from the 2015–16 Malawi demographic and health survey

Abstract: Strategies aimed at increasing further uptake of rotavirus and pneumococcal vaccines should target uneducation women to improve health knowledge on vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The non-uptake of both NVIs also varied throughout the regions. This finding was in line with multiple studies that have found residence to be a factor in vaccination uptake and coverage [11][12][13][14][15]. Stratified analyses for the RV resulted in small sample sizes which may have led to imprecise confidence intervals for some estimates.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The non-uptake of both NVIs also varied throughout the regions. This finding was in line with multiple studies that have found residence to be a factor in vaccination uptake and coverage [11][12][13][14][15]. Stratified analyses for the RV resulted in small sample sizes which may have led to imprecise confidence intervals for some estimates.…”
Section: Discussionsupporting
confidence: 87%
“…A proper assessment of NVIs should include examining factors associated with uptake to identify potential areas for interventions in order to increase coverage. Previously established factors include structural issues related to immunization programs [8][9][10], residence [11][12][13][14][15], socioeconomic status [13,[16][17][18], parental education [14,16], and siblingship [12,16,[18][19][20]. The COVID-19 pandemic has greatly impacted individuals' wellbeing and further revealed the importance of understanding drivers of vaccine uptake.…”
Section: Introductionmentioning
confidence: 99%
“…This makes it even more difficult to provide vaccination services. Regional variation of immunization coverage within a country has also been documented in several studies from other developing countries [18, 24, 30, 32–34].…”
Section: Discussionmentioning
confidence: 82%
“…Compared to the two-dose RVV, there is a higher possibility of dropout for the three-dose PCV [29]. Slight differences in coverage between the two vaccines have also been noted elsewhere [30]. According to the EDHS report, the coverage also varies between other vaccines included in the routine EPI schedule in Ethiopia [15].…”
Section: Discussionmentioning
confidence: 99%
“…For example, measles-vaccine uptake in 2019 was estimated to be 92% for the rst dose but only 75% for the second dose (WHO, 2020b; Chirwa et al, 2020). There has overall been a good vaccine uptake for newly introduced immunisations such as the rotavirus (91%) and pneumococcal vaccine (89%) (Ntenda et al, 2019); however, HPV vaccination showed a drop from the rst to the second dose, for example, in the districts of Rumphi (98% to 88%) and Zomba (89% to 76%) (MOH, 2014(MOH, , 2019. In general, less than 70% of eligible children received at least one vaccine dose despite availability; meanwhile, over 90% of eligible caregivers who are in-and out-patients on nonvaccination visits to hospitals have missed at least one vaccination, while about 60% missed more (Ogbuanu et al, 2019;Okeibunor et al, 2018).…”
Section: Introductionmentioning
confidence: 99%